Analisis Input–Output Dampak Fasilitas PPnBM Kendaraan Bermotor DTP Tahun 2021 terhadap Penggandaan Output dan Kesempatan Kerja - Wahyudi, Nico (Universitas Medan Area, 2026)
The COVID-19 pandemic significantly affected Indonesia’s economy, particularly the automotive sector, which experienced a sharp decline due to weakened consumer purchasing power. To support economic recovery and stimulate domestic demand, the government implemented a policy in 2021 providing a Government-Borne Luxury Goods Sales Tax incentive (PPnBM DTP) for motor vehicles. This study aims to analyze the impact of this policy on economic output multipliers and employment creation in Indonesia. This research employs an input–output analysis using the 2016 Indonesian Input–Output Table, which is aggregated into 17 economic sectors. The policy impact is examined through a simulation of a final demand shock derived from the estimated increase in motor vehicle sales benefiting from the PPnBM DTP incentive. The results indicate that an increase in final demand of IDR 45.40 trillion in the wholesale and retail trade; repair of motor vehicles and motorcycles sector generates an additional total economic output of IDR 65.28 trillion. Furthermore, the policy's multiplier effect is estimated to create 567,154 new employment opportunities across various economic sectors. The largest contribution occurs in the automotive trade sector, with significant spillover effects to the manufacturing industry, financial and insurance services, and transportation and warehousing sectors. These findings suggest that the 2021 PPnBM DTP incentive policy played an important role in stimulating economic activity and increasing employment absorption during the post-pandemic economic recovery period